Discourse appropriation and category boundary work: casual teachers in the market. Issue 4 (4th July 2017) - Charteris, Jennifer; Jenkins, Kathryn; Jones, Marguerite; Bannister-Tyrrell, Michelle
ABSTRACT: With the increasing casualisation of the teacher labour force, there is little written on the experiences of casual teachers and the challenges they face in brokering professional identities within constantly shifting and uncertain work contexts. Being a category bound casual teacher (a product of category boundary work) is a complex subject position. The aim of this article is to advance our understandings of the identity work inherent in casual relief teachers (CRTs) performativity. Anti-essentialist theories support this exploration of CRT subjectivities and processes of discourse appropriation. Using collective biography methodology as re-storied memory work, this article speaks back to neoliberal politics of casualisation. The stories draw attention to how both experienced practitioners and newly graduated teachers might 'do' category boundary work within the complexity of school politics as they navigate the uncertainty of gaining and maintaining employment in the Education market.